A Descriptive Study on the Seventh Grade students’ Reading Comprehension Achievement at SMP SUNAN GIRI CLURING in the 2013/2014 Academic Year - Yuanita, Tersia Dara (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
In this research, the researcher wanted to describe about the students’reading comprehension achievement. This research design was applied ondescriptive quantitative research. The respondent was the seventh classstudents at SMP Sunan Giri CLuring in 2013/2014 Academic Year. The totalrespondent was 22 students from one class determined through population. The primary data was a reading comprehension test as an achievement testin the form of multiple choices. The result was analyzed statistically inpercentage then descriptively which presented the students’ scores for theirachievement in Literal Reading Comprehension, and Inferential ReadingComprehension. The secondary data was taken from the documentationand interview. The results of the research showed that the seventh class students’ achievement in reading comprehension is good (73,4%). The details are good(75,4%) for Literal Reading comprehension. And was fair (67,2%) for InferentialReading comprehension. The students get the lowest achievement for Inferential ReadingComprehension and the highest achievement for Literal ReadingComprehension. The students need to improve their vocabulary in order tomake them easier in reading comprehension especially for InferentialReading Comprehension.